Molecular detection and identification of three intracellular parasites of retail mutton products in Beijing, China - Zhu, Zifu; Chen, Yajie; Yang, Xu; Wang, Lifang; Liu, Qun; Liu, Jing (Frontiers in Veterinary Science, 2022)
Sarcocystis spp., Neospora caninum and Toxoplasma gondii are globally ubiquitous pathogens, and domestic sheep are considered to be one of the intermediate hosts. 83 myocardial samples of sheep were collected from 12 retail stores in Beijing, China. Sarcocystis spp., N. caninum and T. gondii were identified by PCR amplification of the 18S rRNA gene, Nc-5 gene and 529bp DNA fragment with a prevalence of 86.7% (95% CI: 77.5-93.2) and 43.4% (95% CI: 32.5-54.7) for Sarcocystis spp. and N. caninum infections, respectively, and no T. gondii was detected. The co-infection prevalence of Sarcocystis and N. caninum was 38.6% (95% CI: 28.1-49.9). Two Sarcocystis species were subtyped by analyzing 18SrRNA sequences and were identified as Sarcocystis tenella and Sarcocystis arieticanis. The prevalence of S. tenella and S. arieticanis infections was 84.3% (95% CI: 74.7-91.4) and 56.6% (95% CI: 45.3-67.5), respectively. Significant differences were observed between S. tenella and S. arieticanis (p<0.01). This indicates that Sarcocystis is prevalent among sheep. These results will provide data support for the prevention and control of sarcocystosis and neosporosis in sheep.